2014
DOI: 10.1001/jama.2014.5555
|View full text |Cite|
|
Sign up to set email alerts
|

Does This Man With Lower Urinary Tract Symptoms Have Bladder Outlet Obstruction?

Abstract: In patients with lower urinary tract symptoms, the symptoms alone are not enough to adequately diagnose bladder outlet obstruction. A bladder scan for urine volume should be performed to assess patients with suspected large postvoid residual volumes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(33 citation statements)
references
References 53 publications
1
26
0
4
Order By: Relevance
“…Nuestros resultados indican un notable efecto de la implantación del ecógrafo en la reducción de los sondajes vesicales por sospecha de retención urinaria. Numerosos estudios han evaluado la fiabilidad y precisión de la ecografía vesical, sin embargo, pocos cuantifican el efecto de disponer de dichos dispositivos (15) . El hecho de disponer de dicho dispositivo supone una reducción, en nuestro caso de casi un 70% del riesgo de SV por sospecha de R.U, lo que sigue la línea de los resultados de Frederickson et al (25) y no solo se reducen los sondajes innecesarios, sino que además se propicia la reducción de efectos no deseados de un SV (26,27) .…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Nuestros resultados indican un notable efecto de la implantación del ecógrafo en la reducción de los sondajes vesicales por sospecha de retención urinaria. Numerosos estudios han evaluado la fiabilidad y precisión de la ecografía vesical, sin embargo, pocos cuantifican el efecto de disponer de dichos dispositivos (15) . El hecho de disponer de dicho dispositivo supone una reducción, en nuestro caso de casi un 70% del riesgo de SV por sospecha de R.U, lo que sigue la línea de los resultados de Frederickson et al (25) y no solo se reducen los sondajes innecesarios, sino que además se propicia la reducción de efectos no deseados de un SV (26,27) .…”
Section: Discussionunclassified
“…Se usa en el 26% de las Unidades de Cuidados Críticos en EEUU (12) . Es un método que es útil en el diagnóstico de retención urinaria tras una cirugía (13) , además, su uso reduce las incidencias de ITU (14) y según la revisión de D'Silva sugiere que debería usarse en pacientes con sospecha de grandes volúmenes residuales post-micción (15) . La utilización de la ecografía volumétrica vesical portátil ha conseguido, por otro lado, aumentar los casos de éxito en sondajes vesicales en pacientes pediátricos en urgencias (16) .…”
Section: Introductionunclassified
“…A systemic review of the diagnostic value of office-based tests for BOO in men with LUTS revealed that individual symptoms and questionnaires for diagnosing BOO are not significantly associated with each other. An IPSS score cutoff of 20 or greater increased the likelihood of BOO [51]. Invasive urodynamic study did change decision making in the management of male LUTS/BPH.…”
Section: Urodynamic Study – Do Men With Lower Urinary Tract Symptoms mentioning
confidence: 99%
“…An IPSS score cutoff of 20 or greater increased the likelihood of BOO [29]. Invasive urodynamic tests did change decision-making in the management of male LUTS.…”
Section: Urodynamic Evaluation Of Bladder Outlet Obstruction In Male mentioning
confidence: 99%